Education as social self - reflection - Hedžet Tóth, Cvetka (Anali PAZU HD, 2022)
Within European Community, it has become increasingly more common to speak of Investment State rather than Welfare State. Likewise, it has become more topical to discuss the change of personality. This is why the present time – narcissistically called the post-historic age, after the end of utopias and after two centuries of revolution and the fall of the socialism of Bolshevik origin (1789-1989) – sees a frequent use of the word individualisation (with a pejorative connotation of extremely non-solidary, egotistic bearing), which has replaced the word society. The reason for this is the basic contention that society as such does not exist. What exists is individuals, and the role of social sciences and humanities mostly implies some kind of control over society. The privatisation process with its affirmative stance toward individualisation has seen many a scholar come to realize that the grinning democracy, clothed in the white robes of artificial smile, is all but a symptom of a repressive society.
Keywords: academic education; Bologna studies; university reform; solidarity; Theodor W. Adorno